Muhammad Abu Zahrah’s legal istinbāṭ on ilḥāq-based nasab establishment for children born of zinā - Ahmad Syaifuddin Al Rosyid; Ahdiyatul Hidayah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
The determination of nasab for children born of zinā through ilḥāq remains a contested issue in Islamic family law. Divergent interpretations of scriptural texts have led Muslim jurists to differ on the validity of paternal acknowledgment and its legal consequences. This study aims to analyze juristic opinions on the establishment of nasab for children born of zinā through ilḥāq, examine Muhammad Abu Zahrah’s position, and explain the legal evidence and methods of istinbāṭ underlying his view. This qualitative library-based study focuses on Abu Zahrah’s legal thought, with data analyzed through thematic analysis and validated through source triangulation and referential adequacy. The findings reveal three main points. First, juristic disagreement indicates that ilḥāq in cases of children born of zinā remains within the domain of ijtihād: some scholars permit it to protect the child’s legal and social interests, whereas others reject paternal attribution because zinā does not constitute a valid basis for establishing nasab. Second, Abu Zahrah permits ilḥāq through acknowledgment by the biological father under specified conditions, particularly where zinā is not explicitly acknowledged, thereby allowing recognition of nasab and establishing maintenance as a consequence of kinship. Third, Abu Zahrah’s istinbāṭ integrates bayānī, taʿlīlī, and istiṣlāḥī reasoning, drawing on the ḥadīth al-firāsh, Qur’anic indications concerning the six-month minimum gestational period, and considerations of the child’s interests. The study concludes that Abu Zahrah’s approach represents an ijtihādī framework that reconciles the legal integrity of nasab with child protection and legal certainty through an integrative maqāṣid al-sharīʿah-oriented approach.